2008
DOI: 10.1080/00365510701496496
|View full text |Cite
|
Sign up to set email alerts
|

Determination of testosterone in serum by liquid chromatography-tandem mass spectrometry

Abstract: Commercial direct immunoassays for serum testosterone sometimes result in inaccuracies in samples from women and children, leading to misdiagnosis and inappropriate treatment. The diagnosis of male hypogonadism also requires an accurate testosterone assay method. We therefore developed a sensitive and specific stable-isotope dilution liquid chromatography-tandem mass spectrometric (LC-MS/MS) method for serum testosterone at the concentrations encountered in women and children. Testosterone was extracted with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Lean body mass (LBM): We believe that this is the key to the difference in strength and performance between men and women as well as to the reason why this new regulation relating to circulating testosterone levels in the blood introduced by IOC/IAAF is based on loose thinking and false pseudo-science. Men have a LBM that is on average 10 kg higher than that of a woman of the same height 3 and this supports Dr Ritzen and colleagues' recent published statement that: 'The world records for men in sports that rely on strength or size are on average 10% better than for women'. 4 Lean body mass is largely determined by height (Fig.…”
Section: )supporting
confidence: 65%
See 1 more Smart Citation
“…Lean body mass (LBM): We believe that this is the key to the difference in strength and performance between men and women as well as to the reason why this new regulation relating to circulating testosterone levels in the blood introduced by IOC/IAAF is based on loose thinking and false pseudo-science. Men have a LBM that is on average 10 kg higher than that of a woman of the same height 3 and this supports Dr Ritzen and colleagues' recent published statement that: 'The world records for men in sports that rely on strength or size are on average 10% better than for women'. 4 Lean body mass is largely determined by height (Fig.…”
Section: )supporting
confidence: 65%
“…The authors do not mention the publications that, under resting conditions, demonstrate no overlap in testosterone levels between healthy men and women. 3 While the IAAF/IOC Regulations state that blood samples must be drawn under resting conditions, Healy et al obtained blood within two hours after completing national or international competitions. Others have shown that following strenuous exercise, testosterone levels in men decrease, while in women, T is unchanged or moderately increased.…”
mentioning
confidence: 99%
“…Sex hormone binding globulin (SHBG) levels were measured using solid-phase, chemiluminescent immunometric assays (Immulite 1000, Diagnostic Products Corporation, Los Angeles, CA, USA). Serum 17β-estradiol (E2) was determined in duplicate by extraction RIA as previously described 17 and testosterone levels as previously described 18 . E2 and testosterone were utilized together with SHBG in calculating the free E2 and free testosterone levels, respectively, according to a previously presented method 19 .…”
Section: Blood Samplingmentioning
confidence: 99%
“…17␤-Estradiol levels were utilized together with SHBG in calculating the free E 2 levels, according to a previously presented method (3). Testosterone was measured as previously described (21).…”
Section: Methodsmentioning
confidence: 99%